The Effectiveness of Breast Care Intervention on Breast Milk Expression in Primiparous Postpartum Mothers - Maya Erisna; Mardelia Astriani; Yusniasih Purwaningrum (Universitas Nurul Jadid Paiton Probolinggo, East Java, Indonesia, 67291, 2025)
Breast milk remains the optimal source of nutrition for infants, providing immunological protection and long-term health benefits for both mother and child. However, many primiparous postpartum mothers experience challenges in achieving adequate breast milk expression. This study aimed to determine the effectiveness of a structured breast care intervention on breast milk expression among primiparous postpartum mothers at a private maternal and child health clinic in Tangerang, Indonesia, conducted between January and March 2025. Using a preexperimental design with a static-group comparison, 40 respondents were selected through non-probability sampling. Statistical analysis using the Mann–Whitney U-Test yielded a pvalue of 0.002, demonstrating a 95% success rate in the intervention group compared to 40% in the control group. These results indicate that breast care interventions significantly improve milk expression among first-time mothers. Integrating this approach into postpartum nursing practice may enhance breastfeeding outcomes and contribute to achieving Sustainable Development Goal (SDG) 3, which promotes maternal and child health.